The great inflation, limited asset markets participation and aggregate demand: FED policy was better than you think - Florin O. Bilbiie (European Central Bank (ECB), 2004)
When enough agents do not participate in asset markets, the slope of the aggregate demand curve is reversed. Monetary policy should be passive, to ensure equilibrium determinacy and to minimize variations in output and inflation. This paper presents evidence that asset markets participation in the US was limited over the Great Inflation period and the slope of the IS curve had the 'wrong' sign. Our results may help explain the 'Great Inflation' and give optimism for FED policy. If the economy was characterized by a relatively higher degree of financial frictions over that period: (i) policy implied a determinate equilibrium and ruled out sunspot fluctuations; (ii) policy was closer to optimal than conventional wisdom dictates; (iii) responses and variability of macroeconomic variables conditional upon fundamental shocks are close to their estimated counterparts for a wide range of reasonable parameterizations. Notably, 'cost-push' shocks are enough to generate a Great Inflation.
Keywords: E31; E32; E44; E58; E65; 330; limited asset markets participation; monetary policy rules; real (in)determinacy; Taylor Principle; the Great Inflation